KEDUDUKAN GUBERNUR SEBELUM DAN SESUDAH AMANDEMEN UNDANG-UNDANG DASAR 1945 - , AL MASUDAH; , Mailinda Eka Yuniza, S.H., LL.M. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Territory autonomy is a transfer of right, authority, and obligation of territory to manage its own domestic issues based on the law. The role of the Government should be emphasized on the national policy, the Province coordinating the implementation of the policy and the regency as the implementer of the policy. This research is intended to review the theoretic approach of governor position according of governor position before and after amandementof UUD1945, to know the benefits and flaws of the governor position along with the solution offered to solve the problem.This research is also intended to fulfill the final project to achieve a magister title from the Faculty of Law, GadjahMada University,Yogyakarta. This research was a normative research and used several approaches, namely: the statute approach, case approach, historical approach, comparative approach, and conseptual approach The position of the Governor in the Indonesian government system before and after the amandement of UUD 1945 holds the position as the vice-seat of government and district head. The Governor, as the district head and representative of the government, serves as a bridge and shortens the span of control to reach the integrity of both planning and implementation in order to reach effectiveness and efficiency of government implementation. However, on its status as territory autonomy, the province authority which is arranged on ordinance is not clear and appears to be overlapping with the authority between the Governor and regent or mayor. In addition to clarifying and affirming the governorâs duty and authority as vice-seat of government, ordinance of local government must determine the pressing of autonomy in the province in order for the outonomy position of regency to be under the province autonomy